ANALISIS PERUBAHAN TINGKAT KEBUTUHAN MODAL USAHA MIKRO KECIL MENENGAH (UMKM) SEBELUM DAN SELAMA PANDEMI COVID-19 - Delvia Ramadhini; Novi Kadewi Sumbawati; U Usman (Jurnal Ekonomi & Bisnis, 2023)
This research aims to examine changes in the level of capital requirements for MSMEs in Labuhan Sumbawa Village before and during the Covid-19 period. The type of this study was comparative research. The type of data used in this study is quantitative data obtained directly through interviews. The informants in this study were 50 MSME actors in Labuhan Sumbawa Village. Data analysis techniques used include paired samples statistics test, paired samples correlations test, and paired samples t-test. Based on the data analysis carried out, it can be concluded that there are differences between the capital requirements of MSMEs in Labuhan Sumbawa Village before and during the Covid-19 pandemic. The Covid-19 pandemic has had a negative impact on the capital requirements of MSMEs in Labuhan Sumbawa Village. The average capital requirement for MSMEs in Labuhan Sumbawa Village has decreased during the Covid-19 pandemic compared to before the Covid-19 pandemic.